The Influence of Organizational Culture and Leadership Style on Employee Job Statisfaction - Melfin Melfin (Greenation Research & Yayasan Global Resarch National, 2025)
The purpose of this research is to understand and analyze: (1) Organizational Culture; (2) Leadership Style; (3) Employee Job Satisfaction; and (4) the Influence of Organizational Culture and Leadership Style on Employee Job Satisfaction at Credit Cooperative X in Bandung City, both simultaneously and partially. The research methods used in this study are descriptive surveys and explanatory surveys, with the unit of analysis being the employees at Credit Cooperative X in Bandung City, with a sample size of 44 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the research results, it was found that the Organizational Culture according to Employees at Credit Cooperative X in Bandung City can generally be considered good; the Leadership Style according to Employees at Credit Cooperative X in Bandung City, it turns out that most employees gave a good response, and the Job Satisfaction of Employees at Credit Cooperative X in Bandung City is currently rated as good. Organizational Culture and Leadership Style simultaneously influence Employee Job Satisfaction at Credit Cooperative X in Bandung City. However, partially, Organizational Culture dominantly influences Employee Job Satisfaction more than Leadership Style. Because Organizational Culture more dominantly influences performance, it becomes the top priority in improving Employee Job Satisfaction. Credit Cooperative X in Bandung City is expected to further improve the conditions and situations at Credit Cooperative X in Bandung City, so that employees can work more professionally and be more motivated.